In situ U–Pb and Lu–Hf isotopic studies of zircons from the Sancheong–Hadong AMCG suite, Yeongnam Massif, Korea: Implications for the petrogenesis of ∼1.86 Ga massif-type anorthosite. (1st May 2017) - Lee, Yuyoung; Cho, Moonsup; Yi, Keewook
Graphical abstract: Highlights: Anorthosite-mangerite-charnockite-granite (AMCG) magmatism at 1.87–1.86 Ga. Episodic AMCG magmatism linked to the North China Craton. Zircon Hf isotopes compatible with the two-source model for the AMCG rocks. Late orogenic AMCG suite associated with the Columbia supercontinent assembly. Abstract: Isotopic and geochemical characteristics of Proterozoic anorthosite-mangerite-charnockite-granite (AMCG) suite have long been used for tracing the mantle–crustal source and magmatic evolution. We analyzed Lu–Hf isotopic compositions of zircon from the Sancheong–Hadong AMCG complex, Yeongnam Massif, Korea, in order to understand tectonomagmatic evolution of the Paleoproterozoic AMCG suite occurring at the southeastern margin of the North China Craton (NCC). The anorthositic rocks in this complex, associated with charnockitic and granitic gneisses, were recrystallized to eradicate magmatic features. In situ SHRIMP (sensitive high-resolution ion microprobe) U–Pb analyses of zircon from a leuconorite and an oxide-bearing gabbroic dyke yielded weighted mean 207 Pb/ 206 Pb ages of 1870 ± 2 Ma and 1861 ± 6 Ma, respectively. Charnockitic, granitic, and porphyroblastic gneisses yielded weighted mean 207 Pb/ 206 Pb zircon ages of 1861 ± 6 Ma, 1872 ± 6 Ma, and 1873 ± 4 Ma, respectively. These crystallization ages, together with our previous geochronological data for anorthosites (1862 ± 2 Ma), are indicative of episodic AMCG magmatism over an ∼10 Ma interval. Initial εHf (t) values of zircon analyzed from five anorthositic rocks and four felsic gneisses range from +2.1 to −6.1 and −0.3 to −5.4, respectively. Zircon Hf isotopic data in combination with available whole rock Sr–Nd isotopic data suggest that anorthositic parental magma was most likely derived from a mantle source and variably affected by crustal contamination. This crustal component is also reflected in charnockitic-granitic magmas produced primarily by the melting of lower crust. Taken together, the AMCG magmatism at 1.87–1.86 Ga in the Yeongnam Massif is most likely a late orogenic product of Paleoproterozoic NCC amalgamation tectonically linked to assembly of the Columbia supercontinent.